Comments on John D. Keen and James E. Keen, What is the point: will screening mammography save my life? BMC Medical Informatics and Decision Making, 2009 - Retsky Michael (BMC Medical Informatics and Decision Making, 2009)
Abstract This paper by John D. Keen and James E. Keen addresses a thorny subject. The numerical findings and commentaries in their paper will be disturbing to some readers and seem to defy logic and well established viewpoints. It may well generate angry letters to the editor. However such numerical analysis and reporting including civil discussion should be welcomed and are the basis for informed decision making – something that is highly needed in this field.